Terapi Aktivitas Kelompok Meronce Tali Sepatu Terhadap Tingkat Stress Pada Lansia Yang Menjalani Perawatan Di Panti Werdha Kasih Ayah Bunda - Sari , Rina Puspita; Aulia, Mustika; Syantira, Putri Amanda; Al Haq, Rifa Asmieza; Febrianty, Sintia; Ashari, Siti Bunga; Hijriatun Nazwah, Siti Nayla; Nuraliza, Siti (Kolaborasi: Jurnal Pengabdian Masyarakat, 2025)
Introduction: The Elderly individuals experience a gradual decline in physical and psychological functions, which can trigger stress. Living in a nursing home without family presence may lead to feelings of loneliness and emotional distress. Non-pharmacological interventions such as group activity therapy are needed to help maintain the mental health of the elderly. One effective method is meronce (bead threading) therapy, which stimulates creativity, encourages social interaction, and helps reduce stress levels. Objective: To determine the effect of group activity therapy using meronce on stress levels in elderly residents at Panti Werdha Kasih Ayah Bunda, Tangerang City. Method: The study involved 14 elderly respondents using the DASS questionnaire to assess stress levels before and after the intervention. A single session of meronce therapy was conducted in group format, followed by a post-test assessment. Result: Before therapy, 6 participants (42.86%) had mild stress and 8 (57.14%) had moderate stress. After therapy, 10 participants (71.43%) had mild stress and only 4 (28.57%) remained with moderate stress. These results indicate a decrease in stress levels following the intervention. Conclusion: : Group activity therapy using meronce is effective in reducing stress levels among elderly residents at Panti Werdha Kasih Ayah Bunda and serves as a preventive approach in elderly mental health care.